Comparação entre a interposição gastrojejunoduodenal e gastrocoloduodenal em cães: aspectos clínicos e anatomopatológicos - Marilles Porto Mattos (2013)
Introduction: The interpositions the intestine are importants in varied operations or digestiv tube. Nevertheless, are possible the complications imediates and without delay. Objective: To compare interpositions with segments the jejunum and colonic in dogs, all that as evolutions clinical them to surgical and anotopathologic there segments the jejunum colonic the intestine. Method: It was used 40 dogs, immunized and dewormed, of the male gender. Age between 36 months and 72 months, weight between 6kg and 16kg., distributed in groups (G1 = 20) and (G2 = 20). Submitted to anesthesia and the surgical procedure to gatroduodenol interposition whit segments the jejunum and colonic between estomach and duedenum . After 120 days, was realization and relatparotomized and jejunum and colonic segments were removed, processed, to Bouin, after that, the histological sections were stained hematoxylin eosin,.for study anatomopathologic. Were analized clinical, surgical. Variables: (weight, diarrhea, fistula, infection, dehiscence, and incisional hernia); aspect anatopathologic (neutrophilic infiltration, increase, in number of calicifom cells and hypotophy of the vilosities and crypts). Statistical analysis used were mensured by Mann-Whitney and Fishers Exact tests .. Results: The dogs submitted to gastrocoloduodenal to produce more waste the weight (p<0,05) the diarrhea (p<0,001) The rate anastomosis fistula in G1 was (20%) and G2 (100%) The infection, dehiscencia and incisional hernia in G1 was (20%) and G2 (100%) . The occurrences hispathologic were too intense in G2 (p<0,001). Conclusion: The study suggest that morbidity associated whit the interposition whit segments the intestine is high, being higher in segments the colonic